2007
DOI: 10.1186/gb-2007-8-10-r206
|View full text |Cite
|
Sign up to set email alerts
|

A genetic code alteration generates a proteome of high diversity in the human pathogen Candida albicans

Abstract: Background: Genetic code alterations have been reported in mitochondrial, prokaryotic, and eukaryotic cytoplasmic translation systems, but their evolution and how organisms cope and survive such dramatic genetic events are not understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
149
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(154 citation statements)
references
References 63 publications
4
149
0
1
Order By: Relevance
“…To increase Leu misincorporation at CUG sites, we have inserted one (strain T1) or two (strain T2) copies of a yeast Leu tDNA CAG Leu gene (25) into the RPS10 genome locus of the Candida albicans SN148 strain (26). This heterologous tRNA CAG Leu misincorporates Leu only at the atypical C. albicans Ser CUGs (23,25). We also knocked out one or two copies of the chromosomal C. albicans Ser tRNA CAG Ser gene in strains T1 and T2, producing strains T1KO1 and T2KO1 or T2KO2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To increase Leu misincorporation at CUG sites, we have inserted one (strain T1) or two (strain T2) copies of a yeast Leu tDNA CAG Leu gene (25) into the RPS10 genome locus of the Candida albicans SN148 strain (26). This heterologous tRNA CAG Leu misincorporates Leu only at the atypical C. albicans Ser CUGs (23,25). We also knocked out one or two copies of the chromosomal C. albicans Ser tRNA CAG Ser gene in strains T1 and T2, producing strains T1KO1 and T2KO1 or T2KO2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Protein X-ray crystallography and molecular modeling showed that the Leu and Ser residues encoded by CUGs are partially exposed to the solvent or on the interface of subunits of protein complexes where they can be better tolerated (24). These structural data explain the high tolerance to CUG ambiguity (23) and are fundamental to rationalize the evolution of CUG reassignment in the fungal CTG clade. However, the dynamic range of Leu misincorporation at CUGs and the selective advantages that it spawns are not fully understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because protein function is dictated by structure and, thus, amino acid sequence, mistakes in translation of the genetic code can yield drastic alterations in the properties of products of mistranslation. Quality control mechanisms exist that help maintain translation fidelity, limiting mistranslation to one mistake in 10 3 -10 4 codons under normal growth conditions (1). The aminoacyl-tRNA synthetase (aaRS) 2 enzymes, which pair amino acids and tRNAs for participation as substrates in protein synthesis, are among the primary determinants of translational fidelity.…”
mentioning
confidence: 99%
“…In the event that a non-cognate amino acid or tRNA is utilized as an aaRS substrate, the resulting mispaired aminoacyl-tRNA (aa-tRNA) species may lead to an error in decoding at the ribosome, resulting in mistranslation of the genetic code. To limit these errors, aaRS enzymes have evolved strict quality control mechanisms, which typically confer high substrate specificity and contribute to an estimated rate of mispaired aatRNA production limited to roughly 1 per 3000 aa-tRNAs produced (2), although deviations exist between species and specific aaRSs (1,3,4). Some aaRS enzymes hydrolyze or selectively release (5) aminoacyl-adenylate (aa-AMP) species resulting from non-cognate amino acid activation in a quality control step before transfer of the aminoacyl moiety to tRNA.…”
mentioning
confidence: 99%